2022
DOI: 10.3390/polym14102116
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Approach for Controlling Black Rot of Persimmon Fruits by Means of Nanobiotechnology from Nanochitosan and Rosmarinic Acid-Mediated Selenium Nanoparticles

Abstract: The protection of persimmon fruits (Diospyros kaki L.) from postharvest fungal infestation with Alternaria alternata (A. alternate; black rot) is a major agricultural and economic demand worldwide. Edible coatings (ECs) based on biopolymers and phytocompounds were proposed to maintain fruit quality, especially with nanomaterials’ applications. Chitosan nanoparticles (NCt), rosmarinic acid bio-mediated selenium nanoparticles (RA/SeNPs) and their composites were produced, characterized and evaluated as ECs for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…When 50% of fruits showed symptoms of shrinkage and/or spoilage, the fruits was considered to have reached the end of its shelf-life (Tolasa et al 2021 ). In general, ripened fruits are more susceptible to pathogen infection and decay faster than green ones (Rodrigues and Kakde 2019 ). The main bioactive compounds in ripened tomato are flavonoids, lycopene, and carotenoids as well as soluble sugars, β-carotene, vitamins, and tomatine.…”
Section: Discussionmentioning
confidence: 99%
“…When 50% of fruits showed symptoms of shrinkage and/or spoilage, the fruits was considered to have reached the end of its shelf-life (Tolasa et al 2021 ). In general, ripened fruits are more susceptible to pathogen infection and decay faster than green ones (Rodrigues and Kakde 2019 ). The main bioactive compounds in ripened tomato are flavonoids, lycopene, and carotenoids as well as soluble sugars, β-carotene, vitamins, and tomatine.…”
Section: Discussionmentioning
confidence: 99%
“…Salem et al [ 82 ] suggested that nano-Se (synthesized by the green method), and nanocomposite agents with fungicidal effects were effective at controlling P. digitatum strains using concentrations of 10–100 µg/ml. SeNPs produced by the green method have been reported to have a wide range of antimicrobial activity against fungal pathogens in food such as Aspergillus brasiliensis , A. flavus , A. oryzae , A. ochraceus , F. anthophilum , and Rhizopus stolonifera [ 83 ], and that the use of very low concentrations of SeNPs synthesized by the green method (100 and 200 ppm) inhibited the growth of Pyricularia grisea [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the CHNPs were combined with metals, such as copper (Eshghi et al., 2014; Meena et al., 2020), titanium(IV) oxide (Helal et al., 2021), iron(III) oxide (Saqib et al., 2019), and selenium (Salem, Abd‑Elraoof, et al., 2022; Salem, Tayel, et al., 2022), while other studies described the combination of the CHNPs with silica (Youssef et al., 2019; Youssef & Roberto, 2020) and graphitic carbon nitride (Ni et al., 2022). In contrast with the addition of essential oils, the addition of metals and inorganic salts did not pose any obvious effect on the size of CHNPs.…”
Section: Combination and Loading Of Chnpsmentioning
confidence: 99%
“…CHNPs have been used for extending the shelf life of different postharvest products (Table 1), including fruits, leaves, such as basil (Hassan et al., 2021), coriander (Ali, Hassan, et al., 2022), lettuce (Paomephan et al., 2018), and marjoram (Amer & Shoala, 2020), flowers, such as roses (Ali, Issa, et al., 2022), and mushrooms (Karimirad et al., 2019, 2020; Karimirad et al., 2018; Karimirad et al., 2018; Valizadeh et al., 2021). The applications of CHNPs in fruits are the most common and cover a wide range of fruit types, including apples (Abdel‐Rahman et al., 2021; Zhao et al., 2021), apricots (Algarni et al., 2022), avocados (Chavez‐Magdaleno et al., 2018; Correa‐Pacheco et al., 2017), bananas (Wantat et al., 2022), blueberries (Medina et al., 2019), cherries (Arabpoor et al., 2021; Ma et al., 2019), chilies (Divya et al., 2018), citrus (Cuong et al., 2022), crabapples (Sun et al., 2020), cucumbers (Cui et al., 2018; Isturiz‐Zapata et al., 2020; Mohammadi et al., 2015b), eggplants (Divya et al., 2018), figs (Aparicio‐Garcia et al., 2021), grapes (Hashim et al., 2019; Silva et al., 2020; Youssef et al., 2019; Youssef et al., 2019), guavas (da Silva et al., 2021), olives (Mohamed et al., 2021), papayas (Allanigue et al., 2017), peppers (Correa‐Pacheco et al., 2021; Gonzalez‐Saucedo et al., 2019; Hernandez‐Lopez et al., 2020; Taheri et al., 2020), persimmons (Nasr et al., 2021; Salem, Tayel, et al., 2022), plums (Mahmoudi et al., 2022), pomegranates (Hasheminejad & Khodaiyan, 2020), raspberries (Ishkeh et al., 2021), strawberries (Hadidi et al., 2021; Hesami et al., 2021; Melo et al., 2018; Mohammadi et al., …”
Section: Effects Of Chnps On Postharvest Productsmentioning
confidence: 99%
See 1 more Smart Citation